Elevated temperature ductility dip in an additively manufactured Al-Cu-Ce alloy. (November 2021) - Bahl, Sumit; Plotkowski, Alex; Sisco, Kevin; Leonard, Donovan N.; Allard, Lawrence F.; Michi, Richard A.; Poplawsky, Jonathan D.; Dehoff, Ryan; Shyam, Amit
Abstract: The deformation and failure mechanisms of Al-9Cu-6Ce (wt%) based alloys fabricated with laser powder bed fusion were investigated from room temperature to 400°C. The yield and ultimate tensile strengths decreased monotonically with increase in temperature, but the tensile elongation dipped unexpectedly at elevated temperatures and exhibited a minimum at 300°C. The dip in tensile elongation occurred with a concomitant dip in strain-rate sensitivity (SRS) of deformation. The as-fabricated alloy microstructure was heterogeneous, and the heat affected zone (HAZ) underneath the melt pool boundary was prone to strain localization. At 300 °C, the reduced SRS promoted the progression of strain localization in the HAZ leading to failure initiation and the dip in tensile elongation. A higher SRS or strain-hardening rate at other temperatures improved the tensile elongation by slowing the progression of strain localization in the HAZ such that failure initiated by other mechanisms elsewhere in the microstructure. Notably, the tensile elongation was limited by the defect structure only in a narrow temperature range (150 - 200 °C) while at other temperatures it was limited by the inherent microstructural features. This investigation exemplifies unexpected deformation and failure mechanisms possible in heterogeneous microstructures that result from additive manufacturing. Graphical abstract: Image, graphical abstract